A Comparative Life Cycle Assessment of Advanced Processes for the Removal of Pharmaceutical Residues in Wastewater A Detailed Analysis Based on a Pre-study by Gryaab at Rya Wastewater Treatment Plant - Andersson, Sara; Karlsson, Maria (My University, 2022)
There are no requirements for wastewater treatment plants to treat pharmaceutical residues today. However, the Swedish Environmental Protection Agency has distributed grants to investigate solutions for improving the aquatic environment. Gryaab received grants in 2019 to examine processes for the removal of pharmaceutical residues. A pre-study including a multicriteria-analysis was conducted where three processes were investigated: ozonation, Pulverized Activated Carbon (PAC), and Granular Activated Carbon (GAC). The result showed the importance of further studies on the processes’ environmental impact, leading to this life cycle assessment (LCA) study. This LCA study analysed the processes from five midpoint impact categories: global warming potential, fossil depletion, energy use, eutrophication potential, and acidification potential. The aim was to provide Gryaab with useful data regarding which of the three processes is the environmentally preferable choice and regarding the major environmental impacts of each advanced process. Furthermore, several sensitivity analyses were made to depict what parts of the advanced processes are most crucial for the total environmental impact. This study included two functional units to enable comparisons with both the pre-study and with other LCA studies. They were: the treatment of Gryaab’s wastewater for the removal of pharmaceutical residues for one year; and the treatment of one m3 of wastewater to this end. The calculations in this LCA were made in the software GaBi 9.2.1 Education, where the three processes and the existing sludge treatment were modelled separately. All flows were added in GaBi per m3 of wastewater and then scaled up for the yearly functional unit. According to the results, ozonation with wind power and the GAC process with renewable GAC, wind power, the largest possible bed volumes, and a regeneration plant at Rya wastewater treatment plant were considered the two most preferable alternatives in terms of environmental impact. Ozonation contributed the most to the midpoint impact category energy use. The PAC process contributed the most to global warming and acidification, while global warming was most significant for the GAC process. The value of using renewable alternatives where it is possible was thus strengthened. However, the environmental benefit of advanced wastewater treatment in comparison to its environmental burden must be further analysed to conclude if an implementation is environmentally advantageous.
Keywords: Gryaab; Rya; WWTP; Advanced wastewater treatment; Life Cycle Assessment; Ozonation; PAC; GAC